Generalized Pustular Psoriasis: A Review on Clinical Characteristics, Diagnosis, and Treatment - Raquel Rivera-Díaz; Esteban Daudén; José Manuel Carrascosa; Pablo de la Cueva; Luis Puig (Adis, Springer Healthcare, 2023)
Abstract Generalized pustular psoriasis (GPP) is a rare, chronic, and severe inflammatory skin disorder characterized by sudden eruption of sterile pustules, often accompanied by systemic inflammation. GPP flares can be life-threatening if untreated, owing to potential serious complications such as sepsis and cardiovascular failure. Diagnosis and clinical measurement of disease severity in GPP are often difficult. Lack of standardized criteria in the international guidelines and the heterogeneity of cutaneous and extracutaneous symptoms make the diagnosis of GPP difficult. Clinical criteria for description and diagnosis of pustular conditions, including GPP, are variable and there is no specific agreement on commonly sustained concepts. Differentiation of GPP from other similar conditions/diseases is important and requires careful assessments. The evidence that supports current topical or systemic therapies is largely based on case reports and small studies. Some biologic agents that target key cytokines involved in the activation of inflammatory pathways have been used as treatments for GPP. Recently, spesolimab, an IL-36R antagonist, has been approved in the USA and Japan for the treatment of GPP flares in adults, but there are no currently approved treatments for GPP in Europe. The IL-36 pathway has recently emerged as a central axis driving the pathogenic inflammatory mechanisms of GPP. Biologic agents that inhibit the IL-36 pathway have shown efficacy and safety in patients with GPP, addressing a generally considered unmet medical need.